Klasyfikacja branżowych rynków pracy w województwie śląskim według podaży pracy i popytu na pracę - Hantke, Witold (The Classification of Branch Labour Markets in Silesian Province According to Job Supply and Demand, 2005)
The Silesian labour market is very differentiated internally. The representatives of particular professions differ from one another in both, the dimension of job supply and demand, as well as their regional structure. In this paper, groups of particular professions have been divided into homogenious classes, using the cluster- and discriminant analysis. Also, applying the techniques of linear ordering, a rank of professions has been created. The carried out researches confirm that simple workers, compared to specialists in different fields, are in the worst situation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 642-652